The Effects of Metropolitan Job Growth on the Size Distribution of Family Income - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1991)
This paper examines how a metropolitan area's job growth affects its income distribution. The research uses annual Current Population Survey data on the income distribution in different metropolitan areas from 1979 through 1988. Faster metropolitan job growth increases real family income in the lowest income quintile by a significantly greater percentage than for the average family. Metropolitan job growth also increases the value of property owned by upper income quintiles, but property value effects are not large enough to offset the progressive effects of growth on labor income. Simulations indicate that economic development programs to increase metropolitan job growth will have a progressive effect if the cost per job created is low, and these costs are financed by personal taxes. But economic development programs with a high cost per job created, or financed by cutting social welfare programs, will have a net negative effect on the lowest income quintile.
Additional information: A revised version of this paper appears in Journal of Regional Science, Vol. 34, No. 4 (November 1994), pp. 483-502.
Keywords: J0; I3; J3; 330; earnings; wages; job; growth; family; income; Bartik; economic; development; urban